2016
DOI: 10.1007/s11071-016-3034-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeted energy transfer and modal energy redistribution in automotive drivetrains

Abstract: The new generations of compact high output power-to-weight ratio internal combustion engines generate broadband torsional oscillations, transmitted to lightly damped drivetrain systems. A novel approach to mitigate these untoward vibrations can be the use of nonlinear absorbers. These act as Nonlinear Energy Sinks (NESs). The NES is coupled to the primary (drivetrain) structure, inducing passive irreversible targeted energy transfer (TET) from the drivetrain system to the NES. During this process, the vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…subject to differential Equations (1), given initial state and the restrictions on the design parameters Equation (14). The Equation (16) express the requirements on the vector of design parameters d * and the vector of generalized coordinates q * (t) to guarantee the best attenuation of oscillation of the torque at the transmission input shaft, and at the same time to minimize the total mass inertia of the vibration absorber.…”
Section: Weight-vibration Pareto Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…subject to differential Equations (1), given initial state and the restrictions on the design parameters Equation (14). The Equation (16) express the requirements on the vector of design parameters d * and the vector of generalized coordinates q * (t) to guarantee the best attenuation of oscillation of the torque at the transmission input shaft, and at the same time to minimize the total mass inertia of the vibration absorber.…”
Section: Weight-vibration Pareto Optimizationmentioning
confidence: 99%
“…The DMF was a subject of intensive research [1][2][3][4][5][6][7][8], and has been used in passenger car since the 1980s [9]. To increase the quality of vibration attenuation, the concept of a DMF began to be modified by incorporating additional spring-mass components by combining with a so-called centrifugal pendulum vibration absorber, and additional absorbers with smooth and non-smooth nonlinearities [9][10][11][12][13][14]. Interesting research is ongoing on the development of controlled DMF for torsional vibration attenuation in powertrain systems using controllable magnetorheological elastomeric springs and an appropriate controller design [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savva et al [16] studied the effect that NES damping has on suppressing torsional vibrations of automotive engines operating at idling conditions. In a numerical study, Motato et al [18] demonstrated the characteristic behaviour of an NES for attenuation of torsional vibration of a vehicle powertrain through energy re-distribution and energy dissipation. Scagliarini et al [19] modelled a spur gear pair under constant excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical solution presented in this work provides a background for the design of alternative torsional vibration absorbers, which has attracted significant attentions recently, especially, the latest research topic on nonlinear energy sinks toward vibration suppression for a broader range of frequencies. [18][19][20] Optimization of the DVA Model of the system Figure 1 shows the model of a linear damped structure considered in this study. The primary system is represented by a shaft with N elements (N degrees of freedom) excited by a time-variant torsional moment M(t).…”
Section: Introductionmentioning
confidence: 99%